Universal Credit: Welfare Reform and Mental Health - Mike Brewer; Thang Dang; Emma Tominey (Institute of Labor Economics (IZA), 2022)
The UK Universal Credit (UC) welfare reform simplified the benefits system whilst strongly incentivising a return to sustainable employment. Exploiting a staggered roll-out, we estimate the differential effect of entering unemployment under UC versus the former system on mental health. Groups with fewer insurance possibilities - single adults and lone parents – experience a mental health deterioration of 8.4-13.9% sd. For couples, UC partially or fully mitigates mental health consequences of unemployment. Exploring mechanisms, for single adults and lone parents, reduced benefit income and strict job search requirements dominate any positive welfare effects of the reduced administrative burden of claiming benefits.
Keywords: D61; I10; I14; I38; 330; welfare reform; mental health; mediation; decomposition; universal credit